Globalisasi, Netwar, dan Isu-Isu Strategis di Asia Pasifik - Bandoro, Bantarto (UI Scholars Hub, 2006)
Nowadays, globalization gives impact to security, either national or international because of developments of science, technology, and human movement. There are five main issue in international society as consequences of globalization, which are drugs dealer, small arms trafficking, infringement of intellectual property rights, people smuggling, and money laundering. Furthermore, there is new terminology, called netwar, which is occured because of the development of information technology and being used to break up the nationaland international security. Basically, a non-traditional security matter is not a new issue. It is just a local issue, which does not get public awareness but globalization has pushed it to come out and sometimes it is believed that it has become a new resource of global threat.